Cognitive function in healthy elderly: secondary analysis of a randomized controlled trial comparing home-based exercises with virtual vs. message supervision - Silva, Juliana Daniele de Araújo; Maranhão , Diógenes Candido Mendes; Pirauá, André Luiz Torres (O Mundo da Saúde, 2023)
The study aimed to compare different supervision strategies during 12 weeks of a home exercise program on the cognitive function of healthy older adults. A clinical trial was conducted in which community-dwelling older adults of both genders participated. They were divided into two groups with different supervision strategies: those virtually supervised by videoconferences during all training sessions or those supervised by text messages. The intervention for both groups consisted of a program offered through video lessons, with a frequency of three weekly sessions and a duration of 12 weeks. Outcomes were assessed remotely via videoconference. The Montreal Cognitive Assessment (MoCA) was used to assess global cognition, and the Stroop test was used for inhibitory control. An intention-to-treat inferential analysis of mixed models by compound symmetry was performed, considering 95% confidence intervals (CI) and a significance level of 5%. Thirty-eight participants were randomized and allocated to one of the groups (81.6% women, mean age 68.39 ± 6.48 years, mean body mass 69.82 ± 12.15 kg, mean height 1.59 ± 0.06 m, mean body mass index of 27.82 ± 4.88 kg/m²; and 94.7% with more than 12 years of study). There were no statistically significant differences between groups (p>0.05), and no effects over time were observed in intra-group comparisons (p>0.05). It was concluded that both supervision methods used in this study did not provide additional cognitive gains to the home exercise program in healthy older adults.